ANALISIS REAL OPTIONS UNTUK INVESTASI PEMBANGUNAN PABRIK BLOCKBOARD DI PT. DAYA SAKTI UNGGUL CORPORINDO UNIT SAMBONG PACITAN - , Yophi Affandi, SIP, Dr. Hardo Basuki, M.Soc. Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
A company in deciding to invest have an option to invest in real assets. A promising investment opportunities should be identified properly. Managers need a proper and unbiased cash flow predictions. However, in practice, the estimation results that have been implemented with an investment feasibility study sometimes do not correspond to reality. Scenario that occurred could be better or worse than the estimates made. The method typically used in the assessment of an investment project is the discounted cash flow method (DCF). However, this method can not be used on projects that take into account managerial flexibility. There are various options that can be run by managers, whereby when the project goes well, there are options to expand, whereas if it goes bad, the project may be reduced or dismissed altogether. Investment projects that can be easily modified in this way more valuable than that do not provide flexibility. So a project that takes into account managerial flexibility, need to be assessed using Real Options. Valuation of real options can be calculated in several ways, namely by using the Black-Scholes model, Monte Carlo Simulation and Binomial Lattice approach. In this thesis, PT. DSUC Unit Sambong Pacitan face a choice to abandon the investment project or continue running it, these options are examined with one real option techniques, namely Abandonment option. The determination of the value of options used is the binomial lattice method. There are six stages in the completion of the case with the binomial lattice method, namely the frame case, identify the input variables, calculate the parameters of the options, building a binomial tree and calculate the value of assets at each node of the binomial tree, calculate the value of options at each node of the tree by backward induction and the last stage is analyzing the results. The research shows if the expected asset value is lower than the strike price of RP. 14.31 billion, PT. DSUC should close the investment project.